Cost per fall: a potentially misleading indicator of burden of disease in health and residential care settings. Issue 1 (26th October 2011) - Haines, Terry P.; Nitz, Jenny; Grieve, Julia; Barker, Anna; Moore, Kirsten; Hill, Keith; Haralambous, Betty; Robinson, Andrew
Abstract Rationale Little scrutiny has been applied to how 'cost per fall' values have been calculated and applied. This paper presents discourse discussing how the cost of fall statistic could potentially be misleading when applied to inpatient health or residential care settings and provides estimates of the cost of falls and cost of falls per person. Method Burden of disease was estimated using a decision tree approach. Data informing the decision tree were drawn from a retrospective audit of 545 falls in a residential care facility, a visual observation study of 46 residents from the same facility and a cohort study of 186 residents from nine different facilities in Australia. Acute care and transportation costs were extracted from the retrospective audit using incident reports and care note review. The distribution of falls per person and associations between falls, fractures and change in resident mobility were extracted from the cohort study. The association between resident mobility and the amount of time required to perform toileting, transfer and dressing activities was extracted from the visual observational study. Results The minimum 'cost per fall' was estimated to be $AUD 841 and the maximum was $AUD 1024. The 'cost of falls per person' estimate was $AUD 1887 (2008 base year). Conclusions This cost per fall estimate was substantially lower than three previous internationally derived estimates possibly as a consequence of how fall data were collected and modelled in these studies. Cost of falls per person may be a preferable statistic for future use.